2021
DOI: 10.1037/ser0000415
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempt survivors’ recommendations for improving mental health treatment for attempt survivors.

Abstract: Research indicates that connection to mental health care services and treatment engagement remain challenges among suicide attempt survivors. One way to improve suicide attempt survivors' experiences with mental health care services is to elicit suggestions directly from attempt survivors regarding how to do so. This study aimed to identify and synthesize suicide attempt survivors' recommendations for how to enhance mental health treatment experiences for attempt survivors. A sample of 329 suicide attempt surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
1
27
0
3
Order By: Relevance
“…However, the study also identified areas for improvement. Our results are consistent with recent research indicating that reducing stigma, comprehensive psychosocial assessment, and addressing structural barriers to accessing care are essential recommendations for improving mental health services for those who have attempted suicide [45]. As part of several actions to improve the pathway, the GCMHSS has recently introduced a new Crisis Stabilization Unit as an alternative to the emergency department for suicidal consumers.…”
Section: Discussionsupporting
confidence: 90%
“…However, the study also identified areas for improvement. Our results are consistent with recent research indicating that reducing stigma, comprehensive psychosocial assessment, and addressing structural barriers to accessing care are essential recommendations for improving mental health services for those who have attempted suicide [45]. As part of several actions to improve the pathway, the GCMHSS has recently introduced a new Crisis Stabilization Unit as an alternative to the emergency department for suicidal consumers.…”
Section: Discussionsupporting
confidence: 90%
“…On average, patients responded with either "usually" or "always" to questions probing how frequently staff involved them in treatment decisions, listened carefully to them, treated them with respect and dignity, and provided reassurance and support. Studies directly surveying those with lived experience with suicidality have identified each of these areas as critical to facilitating positive treatment experiences (Berg et al, 2017;Hom et al, 2020). The involvement of patients with SI in their treatment decisions has also been cited as a critical avenue by which to improve care for this population (Britton et al, 2008).…”
Section: Aim 3: Comparing Beliefs About Treatment and Patient Satisfactionmentioning
confidence: 99%
“…Over time, these patients-who already had somewhat positive views about We cannot conclude from our data which PHP components were most therapeutic. Yet, many factors considered important when providing high-quality care to individuals with recent SI are present at the PHP, including skills-based therapy, providers experienced with suicide risk management, a multidisciplinary approach, and peer support opportunities (Hom et al, 2020). Consequently, it is possible that some, all, and/or the interaction of these factors contributed to positive perceptions of care-research is needed in this regard.…”
Section: Aim 3: Comparing Beliefs About Treatment and Patient Satisfactionmentioning
confidence: 99%
“…Promising approaches include motivational interviewing‐based interventions that address at‐risk individuals’ specific concerns about help‐seeking (e.g., King et al, 2015) and Web‐based screening interventions that encourage the pursuit of in‐person care (e.g., Haas et al, 2008). Also integral to this work is the perspective of those with lived experience; their recommendations may shed light on why poor treatment engagement and outcomes persist despite initiation of care (see Hom et al, 2020, for suicide attempt survivors’ recommendations on how to improve mental health treatment for attempt survivors at large). We would be remiss not to acknowledge that access to care and a lack of provider training in suicide risk assessment and management are additional challenges that must be considered (see Hom et al, 2015, for review).…”
Section: Applications For Research On Help‐seeking and Mental Health mentioning
confidence: 99%